Spinal muscular atrophy: untangling the knot?. Issue 1 (1st January 1999) - Biros, Ivan; Forrest, Susan
Abstract : Spinal muscular atrophy (SMA), a clinically and genetically heterogeneous group of neuromuscular diseases, is a disorder of motor neurones characterised by degeneration of spinal cord anterior horn cells and muscular atrophy. SMA is an autosomal recessive disorder with a carrier frequency of about 1/50. Three candidate genes, the survival motor neurone (SMN) gene, the neuronal inhibitory protein (NAIP) gene, and the p44 (subunit of basal transcription factor TFIIH) gene, have been considered as genes involved in this condition. The region spanning these genes has a complex organisation including duplications, repetitive sequences, truncated genes, and pseudogenes, which makes molecular analysis of this condition difficult. Although deletions have been found in the majority of SMA patients, a few microrearrangements (like duplications, missense mutations, microdeletions, and gene conversions) localised in the telomeric form of the SMN gene have also been reported. The function of the protein encoded by the SMN gene is still not fully understood but recent studies have indicated that it is found intracellularly in gems, novel nuclear structures. Its interaction with other proteins suggests a role in mRNA processing and metabolism. Whether the NAIP gene protein and other apoptosis associated proteins are directly involved in the initial stages of neurone degeneration and apoptosis, or acting downstream on the pathological pathway, has been difficult to determine. Further studies will be required to elucidate possible functional interactions between these proteins.